2010
DOI: 10.1093/molehr/gaq040
|View full text |Cite
|
Sign up to set email alerts
|

Association between amino acid turnover and chromosome aneuploidy during human preimplantation embryo development in vitro

Abstract: This study investigated the relationship between human preimplantation embryo metabolism and aneuploidy rates during development in vitro. One hundred and eighty-eight fresh and cryopreserved embryos from 59 patients (33.9 +/- 0.6 years) were cultured for 2-5 days. The turnover of 18 amino acids was measured in spent media by high-performance liquid chromatography. Embryos were either fixed for interphase fluorescent in situ hybridization analysis of chromosomes 13, 18, 19, 21, X or Y, or were assayed for mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 115 publications
4
62
0
Order By: Relevance
“…As in the present study, physiological, environmental, or clinical factors can decrease ΔΨm in human oocytes and early embryos, which is one of proposed causes of their compromised quality and IVF outcome. These factors include advanced age of women [34,52], clinical hyperstimulation protocol [8], cryopreservation [20], and the condition of in vitro culture [53]. Therefore, Δ<m-promoting effects of Ax in challenged conditions shown in the present study may be applicable for ameliorating the effects of deleterious factors involved in human IVF.…”
Section: Discussionmentioning
confidence: 78%
“…As in the present study, physiological, environmental, or clinical factors can decrease ΔΨm in human oocytes and early embryos, which is one of proposed causes of their compromised quality and IVF outcome. These factors include advanced age of women [34,52], clinical hyperstimulation protocol [8], cryopreservation [20], and the condition of in vitro culture [53]. Therefore, Δ<m-promoting effects of Ax in challenged conditions shown in the present study may be applicable for ameliorating the effects of deleterious factors involved in human IVF.…”
Section: Discussionmentioning
confidence: 78%
“…Metabolic studies -which initially used radiolabelled substrates-made it possible to define the and is providing insights into the amino acids utilized by healthy oocytes (Hemmings et al, 2012). Indeed, in pre-implantation embryos the quantification of amino acid and energy metabolism is emerging as a potential non-invasive tool with which to assess embryo developmental competence and even pregnancy outcome Picton et al, 2010;Gardner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on pyruvate metabolism showed that increased uptake is correlated with embryo development, but the overall results were inconsistent [24-27, 11, 3, 28]. Glucose consumption was associated with blastocyst development [10]; however, other reports failed to demonstrate this relationship [27,11,29]. Studies regarding oxygen as a metabolite in the oocytes' fertilization environment, found an association between oxygen consumption embryonic development and implantation [13].…”
Section: Discussionmentioning
confidence: 99%